A cross sectional evaluation of an alcohol intervention targeting young university students - Burns, Sharyn; Jancey, Jonine; Crawford, Gemma; Hallett, Jonathan; Portsmouth, Linda; Longo, J. (BioMed Central Ltd, 2016)
BACKGROUND: Hazardous drinking has been found to be higher among young university students compared to their non-university peers. Although young university students are exposed to new and exciting experiences, including greater availability and emphasis on social functions involving alcohol there are few multi strategy comprehensive interventions aimed at reducing alcohol-related harms. METHODS: Random cross sectional online surveys were administered to 18-24 year old students studying at the main campus of a large metropolitan university in Perth, Western Australia. Prior to the completion of the second survey an alcohol intervention was implemented on campus. Completed surveys were received from 2465 (Baseline; T1) and 2422 (Post Year 1: T2) students. Students who consumed alcohol in the past 12 months were categorised as low risk or hazardous drinkers using the Alcohol Use Disorders Identification Test (AUDIT). Due to the cross sectional nature of the two samples two-tailed two-proportion z-test and two sample t-tests were employed to determine statistical significance between the two time periods for categorical and continuous variables respectively. RESULTS: At T1 and T2 89.1 % and 87.2 % of the total sample reported drinking alcohol in the past month respectively. Hazardous levels of alcohol consumption reduced slightly between T1 (39.7 %) and T2 (38 %). In both time periods hazardous drinkers reported significantly higher mean scores for experienced harm, second-hand harm and witnessed harm scores compared to low risk drinkers (p <0.001). Hazardous drinkers were significantly more likely to experience academic problems due to their alcohol consumption and to report more positive alcohol expectations than low risk drinkers at both time periods (p <0.001). CONCLUSIONS: Harms and problems for students who report hazardous drinking are of concern and efforts should be made to ensure integrated and targeted strategies reach higher risk students and focus on specific issues such as driving while intoxicated and alcohol related unplanned sexual activity. However there is also a need for universal strategies targeting all students and low risk drinkers as they too are exposed to alcohol harms within the drinking and social environment. Changing the culture of the university environment is a long term aim and to effect change a sustained combination of organisational actions, partnerships and educational actions is required.